The Gangulis Double Consciousness Through Literacy Practices in Jhumpa Lahiris The Namesake - ERIKA PUTRI RAMADHANI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
ABSTRACT The Gangulis Double Consciousness through Literacy Practices in Jhumpa Lahiri’s The Namesake Name : Erika Putri Ramadhani Reg. Number : 14020154020 Study Program/Year : S1 English Literature/ 2014 Faculty : Languages and Arts Institution : State University of Surabaya Advisor : Pratiwi Retnaningdyah Ph.D. This study analyses Ashima’s double consciousness that has been depicted through literacy practices. Literacy practices which considered with texts, pictures, colors, songs, food recipes and fabrics are concerned as communicative forms which can uncover the details of Ashima’s double vision that becomes one in her as an Indian American. Double consciousness is the mingle feeling as the way to perceiving two different cultures of hers. This research aimed to give the literacy knowledge which represented into literary works through introducing the literacy practices as the multimodality that can be the media to deliver the information and observe the character’s background of knowledge. This research examines two research questions. First is discussing how is Ashima’s double consciousness depicted through multimodal literacy practices and second is explaining how does Ashima’s responses to the double consciousness in Jhumpa Lahiri’s The Namesake. Based on the analyses this study reveal that Ashima’s double consciousness is depicting through Desh magazine and silk Sari. Reading Indian magazine and not the other famous women magazine in America as the way she negotiates her double consciousness. Wearing silk Sari for most in her everyday life also shows her Indian sense is more dominant compared with her American culture. While Ashima’s responses her double consciousness as being a wife is reflecting through her Indian food recipe and as being a mother is depicting when she raising her son as Bilingual. Keywords: double consciousness, multimodality of literacy practices, Indian diaspora. ABSTRAK Kesadaran Ganda Karakter Ganguli Ditunjukkan Melalui Artefak Keaksaraan dalam Novel The Namesake Karya Jhumpa Lahiri Name : Erika Putri Ramadhani Nomer Regristrasi : 14020154020 Program Studi/Tahun : S1 English Literature/ 2014 Fakultas : Languages and Arts Institusi : State University of Surabaya Dosen pembimbing : Pratiwi Retnaningdyah Ph.D. Penelitian ini membahas tentang kesadaran ganda Ashima yang tergambarkan oleh artefak keaksaraan. Artefak keaksaraan yang terdiri dari teks, gambar, warna, lagu, resep masakan dan kain/baju dimaknai sebagai media komunikasi yang dapat menjelaskan mengenai pandangan ganda Ashima sebagai seorang India Amerika. Kesadaran ganda disini adalah perasaan campur aduk sebagai proses penjelasan perasaan Ashima tentang dua budaya berbeda yang ada padanya. Penelitian ini bertujuan untuk memberikan pengetahuan keaksaraan sastra melalui pengenalan artefak keaksaraan sebagai media untuk memberikan informasi dan analisa ilmu latar belakang dari seorang karakter. Penelitian ini meneliti dua pertanyaan yang dijadikan riset masalah dalam pembahasan. Pertama membahas tentang bagaimana kesadaran ganda Ashima terambarkan memalui artefak keaksaraan dan yang kedua menjelaskan bagaimana respon Ashima mengenai kesadaran ganda yang dimilikinya dalam novel The Namesake karya dari Jhumpa Lahiri. Berdasarkan pembahasan analisis dapat diketahui bahwa kesadaran ganda Ashima tergambarkan melalui majalah Desh dan baju tradisional India, Sari sutera. Memilih untuk membaca majalah India dan bukannya majalah wanita terkenal di Amerika sebagai cara Ashima dalam menggambarkan kesadaran ganda. Mengenakan baju Sari sutera hamper di setiap harinya menunjukkan sisi India Ashima yang lebih dominan dibandingkan budaya Amerika Ashima. Sedangkan respon Ashima mengenai kesadaran ganda sebagai seorang istri tergambarkan melalui resep masakan Indianya dan sebagai seorang ibu tergambarkan ketika dia membesarkan anak lelakinya sebagai seseorang yang pandai dalam dua bahasa. Kata Kunci: kesadaran ganda, multimodal artefak keaksaraan sastra, diaspor India.